Kepemimpinan Dalam Islam - Chaliddin Chaliddin; Munawar Khalil (Siyasah Wa Qanuniyah, 2023)
This paper aims to explore the concept of leadership in Islam. The research employs a library research method by gathering various written sources and references to reach specific conclusions. Leadership is defined as the method of leading a group, while Islamic leadership is based on the teachings of the Quran and Sunnah. This paper explains that Islamic leadership has specific duties and obligations that must be observed by the leader. It also discusses the characteristics of an Islamic leader and the principles of Islamic leadership. Islamic leadership plays a crucial role in ensuring that a leader follows the commands of Allah SWT and the Prophet Muhammad SAW. What is observed by Muslims, particularly in the actions of a leader, can influence the alignment and trust of the followers in their leadership.